ANALISIS PENGARUH CAR, NIM, BOPO, NPL DAN LDR TERHADAP KINERJA KEUANGAN PERBANKAN SELAMA PANDEMI COVID-19 (Studi Pada Bank Umum yang terdaftar di Bursa Efek Indonesia Periode 2019-2021) - Novita Widyaningsih; Raden Djoko Sampurno (Diponegoro Journal of Management, 2022)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Operating Expenses on Operating Income (BOPO), Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) on banking financial performance during the COVID-19 pandemic as measured by Return on Asset (ROA) This Study was conducted using multiple linear regression method and using IBM SPSS 26 software to analyze the effect of CAR, NIM, BOPO, NPL and LDR on banking financial performance during COVID-19 pandemic. This study uses secondary data obtained by the quartely publication reports of commercial banks listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sample selection in the study was carried out using purposive sampling method an the research sample obtain was 23 banks with 138 observation. The results of the study showed that the Operating Expenses on Operating Income (BOPO) and Capital Adequacy Ratio (CAR) had a negative and significant effect on Return On Asset (ROA). The effect of BOPO on ROA has the greatest value compared to other financial ratios. Net Interest Margin (NIM) has a positive and significant on Return On Asset (ROA). Non Performing Loans (NPL) dan Loan to Deposit Ratio (LDR) each have a negative and positive effect on Return On Asset (ROA), but both are not significant. The effect of LDR on ROA has the smallest value compared to other financial ratios